Job Ladder and Wealth Dynamics in General Equilibrium - Leo Kaas; Etienne Lalé; Nawid Siassi (Institute of Labor Economics (IZA), 2023)
This paper develops a macroeconomic model that combines an incomplete-markets overlapping-generations economy with a job ladder featuring sequential wage bargaining, endogenous search effort of employed and non-employed workers, and differences in match quality. The calibrated model offers a good fit to the empirical age profiles of search activity, job-finding rates, wages and savings, so that we use the model to examine the role of age and wealth for worker flows and for the consequences of job loss. We further analyze the impact of unemployment insurance and progressive taxation for labor market dynamics and aggregate economic activity via capital, employment and labor efficiency channels. Lower unemployment benefits or a less progressive tax schedule bring about welfare losses for a newborn worker household.
Keywords: E21; E24; H24; J64; J65; 330; search and matching; job-to-job transitions; incomplete markets; overlapping generations; wealth accumulation